Examination of return predictability on the Trinidad and Tobago stock exchange - Singh, Roopnarine Oumade (ISER MonaJA, 1993)
Examines weak form capital market efficiency on the Trinidad and Tobago stock exchange. Also presents a review of the capital market efficiency literature.